microRNAs and Their Roles in Plant Development - Dong, Qingkun; Hu, Binbin; Zhang, Cui (Frontiers in Plant Science, 2022)
Small RNAs are a type of small non-coding RNAs with a length of 20-24 nucleotides, of which microRNAs (miRNAs) play a distinct role in plant development. MiRNAs control target gene expression at the post-transcriptional level, through direct cleavage or inhibition of translation. MiRNAs participate in nearly all the developmental processes in plant, such as juvenile-to-adult transition, shoot apical meristem （SAM） development, leaf morphogenesis, floral organ formation and flowering time determination. This review summarizes the latest research progress in miRNA-mediated gene regulation and its role in plant development, to provide the basis for a further in-depth exploration regarding the function of miRNAs and the clarification of the molecular mechanism underlying the interaction of miRNAs and other pathways.